Switching off automatic pilot to promote wellbeing and performance in the workplace: the role of mindfulness and basic psychological needs satisfaction - Guertin, Rachel; Malo, Marie; Gilbert, Marie-Hélène (Frontiers in Psychology, 2023)
Building on self-determination theory, this study aims to advance the happy-productive worker thesis by examining a sequential mediation linking trait mindfulness to task performance through basic psychological need satisfaction and psychological well-being at work. Whereas most of the papers published on the topic stem from USA and Europe, we tested our model in a Canadian sample of 283 French-speaking workers. Based on structural equation modeling, results show that the three need satisfactions at work mediate the relationship between trait mindfulness and psychological well-being at work. Rather than observing a sequential mediation, we find an indirect effect of trait mindfulness on task performance through the satisfaction for one of the basic psychological need (i.e., competence). The present research goes beyond previous studies by exploring a new pair of happy construct-productive criteria alongside an emergent intrapersonal factor contributing to this relationship.